2016
DOI: 10.12659/msm.895853
|View full text |Cite
|
Sign up to set email alerts
|

Effects of siRNA-Mediated Knockdown of HDAC1 on the Biological Behavior of Esophageal Carcinoma Cell Lines

Abstract: BackgroundHDAC1 has been shown to be closely associated with the occurrence of tumors. We aimed to investigate the effects of siRNA-mediated HDAC1 knockdown on the biological behavior of esophageal carcinoma cell lines.Material/MethodsHDAC1 expression in esophageal cancer cell lines TE-1, Eca109, and EC9706 was compared by Western blot analysis. These cells were transfected with siRNA-HDAC1 and cell proliferation was evaluated by MTT assay to select the optimum cell line for subsequent experiments. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Thus, the pro-apoptotic effect of miRNA-370 is functioned through these factors. Furthermore, the current study showed that the overexpression of miRNA-370 increased the expression of CyclinD1, p21 and p27, which are related to the regulation of cell cycle progression (19,20).…”
Section: Discussionmentioning
confidence: 54%
“…Thus, the pro-apoptotic effect of miRNA-370 is functioned through these factors. Furthermore, the current study showed that the overexpression of miRNA-370 increased the expression of CyclinD1, p21 and p27, which are related to the regulation of cell cycle progression (19,20).…”
Section: Discussionmentioning
confidence: 54%
“…1B). As the first protein synthesized in the G1 phase, cyclinD1 acts a crucial role in cell cycle progression from G0/G1 phase to S phase [23]. Therefore, the down-regulation of cyclinD1 induced by propofol indicated an anti-proliferative role.…”
Section: Propofol Inhibits Cell Proliferation Of Hepg2 and Smmc-7721 mentioning
confidence: 99%
“…For example, HDAC1 has been demonstrated to be tumor promoter in a range of malignancies, covering gastrointestinal tumors such as colorectal cancer [ 18 ], and gastric cancer [ 19 ], as well as HCC [ 20 ] and ovarian cancer [ 21 ]. Inhibition of this HDAC has recently been corroborated to prevent the progression of gastric cancer [ 22 ] and esophageal carcinoma [ 23 ]. The major results from the present study revealed that HDAC1 was highly expressed in CC clinical samples and cells, whereas shRNA-induced silencing of HDAC1 contributed to prevention against CC progression, supported by the restrained proliferative, migratory and invasive capabilities of CC cells.…”
Section: Discussionmentioning
confidence: 99%